515 Targeting negative-self-referential processing with transcranial magnetic stimulation: Feasibility studies - Susan Conroy; Ho-Ching (Shawn) Wang; Yu-Chien Wu; Stephen Strakowski; Paul Holtzheimer (Journal of Clinical and Translational Science)
Objectives/Goals: Neuromodulation strategies like transcranial magnetic stimulation (TMS) can target specific neural circuits underlying particular psychiatric symptoms, potentially 1) enhancing understanding of mechanisms of illness and recovery and 2) acting as novel therapeutics. These feasibility studies lay foundation for a study of major depression. Methods/Study Population: Four healthy volunteers completed structural and functional MRI (fMRI). fMRI included a trait-adjective task, a negative self-referential processing task known to activate VMPFC, which is known to be abnormal in major depression. During the task, participants respond on a task pad whether they feel that each of a series of displayed adjectives (positive, negative, or neutral) applies to them. Three participants then participated in a simulated image-guided TMS session using their MRI data to target their VMPFC. Three-dimensional tracking of the participant’s head and the TMS coil was used to position the coil for peak stimulation of the targeted brain region. Results/Anticipated Results: Our team collected quality neural and behavioral data on the fMRI task; participants reported a tolerable experience. Simulated neuronavigated TMS showed feasibility and tolerability of positioning the device to stimulate VMPFC. The fMRI task activated the VMPFC as predicted. The MRI and TMS protocols were replicable and tolerable. These procedures can now be used experimentally by our team with confidence to test our hypothesis that targeting the VMPFC within the brain’s default-mode network may normalize aberrant VMPFC activity seen in major depression, thereby improving excessive negative self-referential processing. Discussion/Significance of Impact: This project lays essential groundwork for my K12 project, “Targeting Negative-Self Referential Processing in Depression with TMS,” a longitudinal neuroimaging and behavioral study using these methods in the study population of people with major depression.